Menuju Pembukuan Secara Akuntabel dan Konsisten - Listya Sugiyarti; Effriyanti Effriyanti (Abdimisi, 2020)
Community service by lecturers and academics who have qualified knowledge can be done to the public at any level, to provide solutions to problems faced with the aim of future improvement. The purpose of community service activities in the playgroup & kindergarten Little Bee House with the concept of "Home me" with the target participants is the POMG committee (Association of Parents and Teachers) in overcoming the problem of organizing documentation of activities that have been carried out both in hard form files and soft files and recording of financial statements in an accountable and consistent manner. Activities in the implementation of community service with the theme Towards Bookkeeping Accountably and Consistently. Dedication activities carried out by the S1 Accounting Study Program of Pamulang University lecturers on October 13-15, 2019 were welcomed by the headmaster of Little Bee House and parents involved in the management of POMG. By using counseling and mentoring methods, this activity is very effective in the form of time and material reception, besides being held indoors, this activity is also carried out in outdoor locations to absorb knowledge more quickly and have more enthusiasm. With the bookkeeping applied so far manually and the average education level of the POMG management is strata 1 level, proving that they need a sustainable mentor. The response of the participants was very good and happy because it was very helpful in learning about managing the accounting and recording of financial accounting in an accountable manner. This activity is expected to provide inspiration and motivation for future lecturers/researchers who will carry out the same/similar and sustainable activities, the knowledge provided can benefit the community, academics, and subsequent writers.